Simons Observatory Focal-Plane Module: Detector Re-biasing With Bias-step Measurements - Wang, Yuhan; Bhandarkar, Tanay; Choi, Steve K; Crowley, Kevin T; Duff, Shannon M; Dutcher, Daniel; Groh, John; Harrington, Kathleen; Healy, Erin; Johnson, Bradley; Lashner, Jack; Li, Yaqiong; et al. (arXiv.org, 2022)
The Simons Observatory is a ground-based cosmic microwave background survey experiment that consists of three 0.5 m small-aperture telescopes and one 6 m large-aperture telescope, sited at an elevation of 5200 m in the Atacama Desert in Chile. SO will deploy 60,000 transition-edge sensor (TES) bolometers in 49 separate focal-plane modules across a suite of four telescopes covering 30/40 GHz low frequency (LF), 90/150 GHz mid frequency (MF), and 220/280 GHz ultra-high frequency (UHF). Each MF and UHF focal-plane module packages 1720 optical detectors spreading across 12 detector bias lines that provide voltage biasing to the detectors. During observation, detectors are subject to varying atmospheric emission and hence need to be re-biased accordingly. The re-biasing process includes measuring the detector properties such as the TES resistance and responsivity in a fast manner. Based on the result, detectors within one bias line then are biased with suitable voltage. Here we describe a technique for re-biasing detectors in the modules using the result from bias-step measurement.